Evaluación de la contracción por secado de concretos de ultra-altas prestaciones con y sin fibras (2020)
In the present investigation, the effect of the incorporation of straight steel fibers and other supplementary cementitious materials (MCS) was evaluated for ultra-high performance concretes (UHPC), added with silica fume. Three UHPC concrete samples were made: the reference sample (composed of cement, silica fume, silica sand, water and superplasticizer additive) and two dosages in which cement and silica fume were partially replaced by supplementary cementitious materials. In sample D2, micro-limestone powder and pulverized glass powder of 28 microns in diameter are added and in sample D3 micro-limestone powder and glass powder of 28 and 7 microns are added as a partial replacement for cement and silica fume. It is sought, on one hand, that reducing the amount of cement in the mix reduces the heat released by the exothermic reaction of the hydration of the cement clinker and, on the other hand, that reducing the amount of silica fume allows reducing the amount of water in the UHPC mix, both effects contribute to the decrease of the drying shrinkage of the concrete. Additionally, the addition of metallic fibers should contribute to absorb the internal tensile forces of the concrete imposed by the contraction of the matrix and due to the high modulus of elasticity of the fibers, prevent large deformations in the concrete mass (Weina Meng, Kamal H. Khayat 2018). The experimental program developed focused on the measurement of drying shrinkage in the first days of concrete age (first 20 days) since the maximum drying shrinkage of UHPC concrete occurs in this period (Hyung Joo Lee, et al., 2019). It was determined that UHPC concrete with partial replacement of hydraulic cement and silica fume by calcium carbonate and 28 micron recycled glass powder, with the incorporation of 2% straight steel fibers over concrete volume, is capable of reducing up to 46% the drying shrinkage of concrete in the first 5 days of age, relative to a reference UHPC concrete. In this mixture, the amount of cement and silica fume was reduced from 852 kg / m³ and 271.7 kg / m³ to 600 kg / m³ and 100 kg / m³ respectively, thanks to the addition of 209 kg / m³ of calcium carbonate and 322.8 kg / m³ of glass powder 28 microns in diameter, supplementary cementing materials at a much lower price.